Expectations Versus Reality in New Cairo's Gated Communities: an Interdisciplinary Analysis of Socio-Spatial Features - Marwan, Ala'a (AUC Knowledge Fountain, 2025)
This research aims to introduce a new framework to identify the disparities between gated community residents’ experiences and real estate developers' visions towards the development. As New Cairo experiences significant growth, many residents are increasingly relocating to gated communities. It has become crucial to assess users’ expectations before moving and their lived experience post-moving to allocate the gaps between their expectations and reality, otherwise, the GC developments will grow apart from users’ updated preferences. The research focuses on the socio-spatial qualities such as accessibility to services and facilities, community interaction, and vast green areas between buildings for privacy, all of which impact housing satisfaction and overall quality of life. The studied socio-spatial factors are investigated through interdisciplinary methods conducted on gated communities’ users and real estate developers’ members. Surveys were conducted on users to assess their socio-spatial experiences, and six semi-structured interviews were conducted with real estate developers to assess their vision for the same studied socio-spatial factors. This research identifies significant gaps between residents' expectations before moving into gated communities and their lived experiences afterward, resulting from differences in property characteristics and economic factors. The findings revealed the indicators of disparities between users’ experiences and developers’ visions, which are a result of differences in priorities and other economic drivers. The analysis suggests that there must be stronger communication between the developers and their residents by including them in the processes in case of any changes in plans. These findings enhance users’ housing satisfaction and quality of life in gated communities.